Notes for the information of members of the committee on the present conditions as to midwifery
1928 1928 1920s 4 pages NOTES FOR THE INFORMATION OF MEMBERS OF THE COMMITTEE ON THE PRESENT CONDITIONS AS TO MIDWIFERY. NUMBER OF BIRTHS. England. Total Births. Notified by Midwives. 1925 655,647 387,658 or 59% 1926. 641,926 383,401 or 60% Wales. 1925. 54,935 90% 1926. 52,637 93% London. 1925. 82,401 51% N.B. In London the lower percentage does not necessarily mean that more women are attended by doctors. The Maternity Wards attached to the Medical Schools take about 3,500 cases and the district cases attended from the Medical Schools are over 6,000, the two together amounting to about 11% of the cases. In the English County Boroughs 70% of births notified by midwives and in the counties 61% so notified. NUMBERS OF MIDWIVES. March 31st 1927. March 31st 1926 Midwives Roll. 63,478 62,680 Of these 46,744 have passed the Board's examination. 9,338 admitted in virtue of prior certification under 1902 Act. 658 admitted through Scottish or Irish certificates. 56,770 6,708 Untrained. 63,478 Expressed in percentage 1927 1926 Trained. 89.4 87.3 Untrained 10.6 12.7 IN PRACTICE. Of the trained women only about 22.5% are in practice. Of the untrained women about 24.3% are in pratice [practice] - though perhaps in infrequent practice. 292/824/1/117